Paradoxical mortality of high estimated glomerular filtration rate reversed by 24‐h urine creatinine excretion rate adjustment: sarcopenia matters - Pei‐Yu Kao; Hung‐Chieh Yeh; Ying‐Fang Hsia; Ya‐Luan Hsiao; Jie‐Sian Wang; David Ray Chang; Shih‐Ni Chang; Hsiu‐Yin Chiang; Chin‐Chi Kuo (Wiley, 2022)
Abstract Background Muscle wasting may explain the paradoxical mortality of patients with high estimated glomerular filtration rates (eGFRs) derived from equation methods. However, empirical evidence and solutions remain insufficient. Methods In this retrospective cohort study, we compared the performance of equation methods for predicting all‐cause mortality; we used 24‐h creatinine clearance (24‐h CrCl), equation‐based eGFRs, and a new eGFR estimating equation weighting for population 24‐h urine creatinine excretion rate (U‐CER). From 2003 to 2018, we identified 4986 patients whose data constituted the first 24‐h CrCl measurement data in the Clinical Research Data Repository of China Medical University Hospital and were followed up for at least 5 years after careful exclusion. Three GFR estimation equations [the Chronic Kidney Disease Epidemiology Collaboration (CKD‐EPI), Modification of Diet in Renal Disease (MDRD) Study, and Taiwanese MDRD], 24‐h CrCl, and 24‐h U‐CER-adjusted eGFR were used. Results A high correlation was observed among the eGFR levels derived from the equation methods (0.995-1.000); however, the correlation decreased to 0.895-0.914 when equation methods were compared with the 24‐h CrCl or 24‐h U‐CER-adjusted equation‐based eGFR. In the Bland-Altman plots, the average discrepancy between the equation methods and the 24‐h CrCl method was close to zero (maximal bias range: 5.12 for the Taiwanese MDRD equation vs. 24‐h CrCl), but the range in limit of agreement was wide, from ±43.7 mL/min/1.73 m2 for the CKD‐EPI equation to ±54.3 mL/min/1.73 m2 for the Taiwanese MDRD equation. A J‐shaped dose-response relationship was observed between all equation‐based eGFRs and all‐cause mortality. Only 24‐h CrCl exhibited a non‐linear negative dose-response relationship with all‐cause mortality. After adjustment for 24‐h U‐CER in the statistical model, the paradoxical increase in mortality risk for an eGFR of >90 mL/min/1.73 m2 returned to null. When 24‐h U‐CER was used directly to correct eGFR, the monotonic non‐linear negative relationship with all‐cause mortality was almost identical to that of 24‐h CrCl. Conclusions The 24‐h U‐CER-adjusted eGFR and 24‐h CrCl are viable options for informing mortality risk. The 24‐h U‐CER adjustment method can be practically implemented to eGFR‐based care and effectively mitigate the inherent confounding biases from individual's muscle mass amount due to both sex and racial differences.